2010
DOI: 10.1128/jvi.01339-10
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Potent d -Peptide HIV-1 Entry Inhibitor with a Strong Barrier to Resistance

Abstract: The HIV gp41 N-trimer pocket region is an ideal viral target because it is extracellular, highly conserved, and essential for viral entry. Here, we report on the design of a pocket-specific D-peptide, PIE12-trimer, that is extraordinarily elusive to resistance and characterize its inhibitory and structural properties. D-Peptides (peptides composed of D-amino acids) are promising therapeutic agents due to their insensitivity to protease degradation. PIE12-trimer was designed using structure-guided mirror-image … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
167
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 146 publications
(180 citation statements)
references
References 60 publications
12
167
0
1
Order By: Relevance
“…4). Prior to selection for in vivo efficacy evaluation here, each inhibitor was shown to efficiently inhibit HIV in vitro (3,5,39,43,50,52,54,56). Our experimental approach for testing these six inhibitors was a single dose of the product administered prior to exposure rather than the two doses of drug administered within 24 h as used in CAPRISA 004 (1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4). Prior to selection for in vivo efficacy evaluation here, each inhibitor was shown to efficiently inhibit HIV in vitro (3,5,39,43,50,52,54,56). Our experimental approach for testing these six inhibitors was a single dose of the product administered prior to exposure rather than the two doses of drug administered within 24 h as used in CAPRISA 004 (1).…”
Section: Resultsmentioning
confidence: 99%
“…PIE12-Trimer is a D-peptide that binds to a conserved pocket on the surface of trimeric gp41. PIE12-Trimer blocks the final stages of the fusion process between the virion and cell membranes (54). TC247 is a thioester compound zinc finger inhibitor that ejects zinc ions from the two HIV nucleocapsid zinc finger loops (32).…”
Section: Vol 85 2011 One Percent Tenofovir Limits Vaginal Hiv Transmentioning
confidence: 99%
“…The results from the single cycle infection assays are presented in Table 2. Compared with T20, SFT displayed more potent inhibitory activity, with mean IC 50 (17)(18)(19)(20)(21). Our previous studies demonstrated that SFT possessed efficient potency to inhibit HIV-1 variants that carry single or double T20-resistant mutations (e.g.…”
Section: Potent Inhibition Of Sft On Diverse Hiv-1 Subtypes Andmentioning
confidence: 99%
“…Among them, T20 (Enfuvirtide, Fuzeon) has been approved for clinical use as the first member of a new class of anti-HIV drugs, HIV fusion inhibitors (9,16,17). This peptide drug can suppress replication of HIV variants with multidrug resistance to reverse transcriptase and protease inhibitors; however, it also easily induces resistance in both clinical settings and laboratory studies (17)(18)(19)(20)(21).…”
mentioning
confidence: 99%
“…Due to great interest in mirror-image proteins as targets for drug discovery (6,7,18,19) and mirror-image synthetic biology (20,21), we were intrigued by the possibility that natural (L-) GroEL/ES could assist in the folding of D-proteins. Thus, we synthesized a D-version of a substrate protein and evaluated its folding by GroEL/ES.…”
mentioning
confidence: 99%